AFGHANISTAN WOMEN'S SPORTS PORTRAIT: VISUAL RHETORIC ANALYSIS OF PHOTOS BY EBRAHIM NOROOZI - Aditya Dwi Putra Bhakti; Ahmad Rizal Dwi Yulianto (Jurnal Partisipatoris, 2023)
Sport is a means for women to voice gender equality, but this is difficult to realize in Afghanistan. To be precise, in 2021, since the Taliban returned to power, women have been banned from participating in sports. Ebrahim Noroozi captured this in a series of photos published on the Associated Press' official website. This study aims to discover the message that Noroozi wants to convey in 15 photographs. This study uses a descriptive qualitative method by utilizing visual rhetorical theory by Foss and Hesford and Brueggemann's rhetorical triangle as data analysis techniques. From the analysis that has been carried out, it is found that this collection of photos is a form of criticism of the conservative policies implemented by the Taliban government which deprived Afghan women of the freedom to engage in sports and the freedom to carry out various other activities. The photographer utilizes a series of photographic techniques to create the illusion of audience intimacy with the phenomenon being raised. These photos were produced with the intention of getting public attention and provoking audiences to act and provide support to Afghan women.